1994
DOI: 10.1176/ajp.151.11.1687
|View full text |Cite
|
Sign up to set email alerts
|

Hopelessness in suicide attempters after acute treatment of major depression in late life

Abstract: The relation between hopelessness and suicide attempts in the elderly was examined by studying the course of hopelessness in depressed patients. Sixty-three elderly patients with recurrent major depression were treated with nortriptyline and interpersonal psychotherapy and underwent serial ratings of hopelessness and depression during the acute and continuation phases of treatment. Patients who had made a suicide attempt in the past had significantly higher hopelessness scores than nonattempters during both ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…This is consistent with both the face-value relatedness of core content of the subscale items, and with multiple studies wherein depression, hopelessness, and anxiety were found to be the most common and strongest predictors of suicidal ideation, suicidal attempt, and suicidal intent [7], [22], [29][31]. Frantic Hopelessness, however, differs from simple anxiety and depression by its sense of urgency.…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with both the face-value relatedness of core content of the subscale items, and with multiple studies wherein depression, hopelessness, and anxiety were found to be the most common and strongest predictors of suicidal ideation, suicidal attempt, and suicidal intent [7], [22], [29][31]. Frantic Hopelessness, however, differs from simple anxiety and depression by its sense of urgency.…”
Section: Discussionsupporting
confidence: 87%
“…Findings indicated that the core schema dimensions of social isolation/alienation, defectiveness/shame, failure, dependence/incompetence, subjugation of needs, emotional inhibition, and unrelenting standards were positively correlated with suicidal ideation. In a sample of individuals with major depression in later life, those who had attempted suicide in the past were more likely to report feelings of hopelessness (Rifai et al, 1994). Furthermore, predictive links have been found between hopelessness and negative self-concept and suicide (Beck and Weishaar, 1990).…”
Section: Gender and Core Beliefsmentioning
confidence: 99%
“…There is disagreement over whether hopelessness is related to suicidal behavior, especially after adjustment for current severity of depression (Kuo et al, 2004;Szanto, Reynolds, Conwell, Begley, & Houck, 1998;Wetzel, 1976). A trait dimension to hopelessness is suggested by its remaining relatively higher in suicide attempters compared with nonattempters, even after depression treatment response (Rifai, George, Stack, Mann, & Reynolds, 1994;Szanto et al, 1998;Young et al, 1996), and there is a stable rank order of hopelessness severity over 2 years in the general population (Young et al, 1996).…”
Section: Introductionmentioning
confidence: 99%